Evaluation of the reducing ability of anion exchange resin AV-17-8 in the sulphite form - Tamazashvili, Anzhela; Makarenko, Iryna (Publishing House of Lviv Polytechnic National University, 2015)
The removal of dissolved oxygen (DO) from water was studied using anion exchange resin AV-17-8 in a sulphite form. The effects of various operating conditions, such as water flow rates, height of the resin bed and mineralization of water on the removal of DO have been studied extensively. It was shown that its reducing ability depends on the water ionic composition that affects the desorption rate of the sulphite anions. The possibility of efficient water deoxygenation at ambient temperature was demonstrated. The mechanism of chlorate anions reduction on the anion exchanger was determined. З використанням аніоніту АВ-17-8 в сульфітній формі вивчено видалення з води розчиненого в ній кисню. Встановлено вплив різних умов експлуатації, таких як витрата води, висота шару завантаження та мінералізація води. Показано, що відновлювальна здатність йоніту залежить від йонного складу води, що визначає ефективність десорбції сульфіт аніонів. Продемонстрована можливість ефективного знекиснення води за температури навколишнього середовища. Встановлено механізм відновлення хлорат аніонів на отриманому аніоніті.
Оцінка відновлювальної здатності аніоніту АВ-17-8 в сульфітній формі
Keywords: dissolved oxygen; anion exchange resin; sulphite; capacity; розчинений кисень; аніоніт; сульфіт; ємність